Corporations, accountability and international criminal law : industry and atrocity - Kyriakakis, Joanna (Edward Elgar Publishing, 2021)
"This timely book explores the prospect of prosecuting corporations or individuals within the business world for conduct amounting to international crime. Joanna Kyriakakis surveys the state of the art in the field, highlighting the case for the international criminal justice project to engage more fully with the role industry can play in atrocity. From the post World War II era to contemporary international criminal courts and tribunals and the activities of domestic criminal justice agencies, this book analyses cases and international law reform efforts aimed at accounting for business involvement in international crimes. The major debates and ensuing challenges are examined, arguing that corporate accountability under international criminal law is crucial in achieving the objectives of international criminal justice. Students, practitioners and academics of international criminal law will find this a beneficial read, particularly through its engagement with the key contemporary debate around the extension of international criminal law to business actors. The exploration of how to address the global governance gap and better account for human rights abuses in transnational corporate activity will also make this an invigorating book for business and human rights scholars"--